Visual Grouping in Accordance With Utterance Planning Facilitates Speech Production - Zhao, Liming; Paterson, Kevin B.; Bai, Xuejun (Frontiers in Psychology, 2018)
Research on language production has focused on the process of utterance planning and involved studying the synchronization between visual gaze and the production of sentences that refer to objects in the immediate visual environment. However, it remains unclear how the visual grouping of these objects might influence this process. To shed light on this issue, the present research examined the effects of the visual grouping of objects in a visual display on utterance planning in two experiments. Participants produced utterances of the form “The snail and the necklace are above/below/on the left/right side of the toothbrush” for objects containing these referents (e.g., a snail, a necklace & a toothbrush). These objects were grouped using classic Gestalt principles of color similarity (Experiment 1) and common region (Experiment 2) so that the induced perceptual grouping was congruent or incongruent with the required phrasal organization. The results showed that speech onset latencies were shorter in congruent than incongruent conditions. The findings therefore reveal that the congruency between the visual grouping of referents and the required phrasal organization can influence speech production. Such findings suggest that, when language is produced in a visual context, speakers make use of both visual and linguistic cues to plan utterances.